ThermodynamicProperties of Nicotinicacid in Dilute HCl and inaqueous NaCl solutions at (293.15, 298.15, 303.15 and 308.15)K (Baghdad Science Journal, 2013)
Apparent molar volume, V?, and viscosity B-coefficient of nicotinc acid in water and in aqueous NaCl solutions have been determined from density and viscosity measurements at (293.15, 298.15, 303.15 and 308.15) K. The experimental density data were evaluated by Masson equation, and the derived, apparent molar volume at infinite dilution, Vo?, and the slope Sv, were interpreted in term of solute-solvent and solute- solute interactions. Transfer apparent molar volumes at infinite dilution of nicotinic acid from water to NaCl solutions at various temperatures have been calculated.The viscosity data have been analyzed using Jones-Dole equation, and the derived parameters, Jones-Dolecoefficient, B,and Falkenhagen coefficient,A, have been also interpreted in terms of solute-solvent and solute-solute interactions respectively. The variation of B coefficient with temperature, (dB/dT), was also determined, the negative values indicate that nicotinic acid in aqueous NaCl solution is structure making. The results were interpreted in terms of complex vitamin-water-co-solute (NaCl) interactions. The free energy, enthalpy, andentropy of activation were calculated using the Nightingale, Benck, and Eyring equations. Free energies of activation of viscous flow ( *1) per mole, and, ( *2) per mole,of solvent and solute, respectively, were also calculated. The effects of soluteson the structure of water were interpreted in terms of viscositiesand the thermodynamic parameters.